Single or triple positivity for antiphospholipid antibodies in “carriers” or symptomatic patients: Untangling the knot - Bertin, Daniel; Camoin‐Jau, Laurence; Veit, Véronique; Resseguier, Noémie; Lambert, Mathilde; Buffet Delmas, Pauline; Heim, Xavier; Mège, Jean‐Louis; Morange, Pierre‐Emmanuel; Bardin, Nathalie (Journal of thrombosis and haemostasis, 2021)
Background Although the triple positivity of antiphospholipid antibodies (aPL) is important for classifying high‐risk patients, interpretation of aPL positivity, namely the lupus anticoagulant (LA), anti‐cardiolipin (aCL), and anti‐beta2‐glycoprotein I autoantibodies (aB2GPI) remains challenging for thrombotic risk stratification. Objective To compare biological and clinical data between triple aPL– and single aCL–positive patients. Methods Of the 6500 patients assayed for aPL in daily practice within 3 years, we retrospectively analyzed data from 161 patients that were either triple aPL–positive or single aCL–positive with 5 years’ follow‐up for 121 of them. Results Whatever triple or single aPL positivity, we found a high prevalence of “carrier” patients (43%), which led us to question the clinical relevance of the triple aPL positivity. This result also justified the need to identify high‐risk profiles. In asymptomatic patients, high risk of thrombotic events is associated with (1) two positive tests for LA or a Rosner Index >27 combined with both aCL‐IgG and aB2GPI‐IgG positivity, (2) persistent single aCL positivity without an associated autoimmune disease. In symptomatic patients, we demonstrated differences in the phenotype of patients and their therapeutic anticoagulation according to the number of positive aPL but we did not find differences in the number of clinical events, recurrence, or relapse, even in the absence of treatment. Conclusion This study shows that the thrombotic risk does not necessarily increase with the number of positive tests and raises the question of the therapeutic management of single aCL–positive patients.